Formulation of metformin-loaded alginate microspheres by ionotropic gelationaerosolization technique - Hariyadi, Dewi Melani; Pathak, Yashwant; Hendradi, Esti; Erawati, Tristiana; Izzatul Hidayah; Santoso, Elizabeth (Penerbit Universiti Kebangsaan Malaysia, 2020)
Metformin hydrochloric acid (HCl)-loaded alginate microspheres prepared using aerosolization method were subsequently evaluated for their physico-chemical characteristics in terms of particle size, morphology, drug loading, entrapment efficiency, yield and in vitro release. A two factorial Design of Experiment (DoE) was used to study the influence of polymer alginate and cross-linker calcium chloride (CaCl2 ) concentrations on microparticle characteristics. The results indicated that all microspheres were spherical in shape, while their particle size was less than 5 µm, although this increased with the intensification of alginate and CaCl2 concentrations. Encapsulation efficiency, loading, and yield were all enhanced by increasing alginate concentration and, conversely, decreasing CaCl2 concentration. The highest encapsulation efficiency, loading, and yield were 40, 31, and 73%, respectively, produced by a formula containing 1.75% alginate and 3% CaCl2 . The drug release of Metformin-loaded microparticles in HCl pH 1.2 ranged from 22 to 28% during a two-hour period, while further drug release of PBS pH 7.4 increased from 67 to 95% over ten hours. The total amount of drug released during a 12-h period increased by reducing alginate concentration. Furthermore, a kinetic study of the dissolution data confirmed the prevalence of a diffusion-controlled mechanism or Higuchi pattern of drug release.